2004
DOI: 10.1242/jeb.01078
|View full text |Cite
|
Sign up to set email alerts
|

A unique visual pigment expressed in green, red and deep-red receptors in the eye of the small white butterfly,Pieris rapae crucivora

Abstract: and III peak at 620·nm and those in type II ommatidia peak at 640·nm. The large shifts of the spectral sensitivities of the R5-8 photoreceptors with respect to the absorption spectrum of their visual pigment can be explained with the spectral filtering by pale-red (PR) and deep-red (DR) screening pigments that are concentrated in clusters of granules near the rhabdom boundary. The peak absorbance of the two spectral filters appears to be approximately 1 (PR) and 2 (DR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 29 publications
4
93
1
Order By: Relevance
“…It is therefore possible that L. rubidus has pentachromatic vision in ventral retina based primarily on four opsins and this pink non-opsin pigment. Filtering pigments of similar effect have been observed for the LW receptors of Papilio xuthus and Pieris rapae (Arikawa et al, 1999;Wakakuwa et al, 2004), and have been shown to be important for butterfly color vision (Zaccardi et al, 2006).…”
Section: Non-overlapping Expression Of Uvrh Brh1 and Brh2mentioning
confidence: 63%
“…It is therefore possible that L. rubidus has pentachromatic vision in ventral retina based primarily on four opsins and this pink non-opsin pigment. Filtering pigments of similar effect have been observed for the LW receptors of Papilio xuthus and Pieris rapae (Arikawa et al, 1999;Wakakuwa et al, 2004), and have been shown to be important for butterfly color vision (Zaccardi et al, 2006).…”
Section: Non-overlapping Expression Of Uvrh Brh1 and Brh2mentioning
confidence: 63%
“…For the filter acting on the R1 and R2 photoreceptors, an effective absorbance of ϳ0.6 follows from Figure 8b. The pigment filter will also act on the proximal photoreceptors, and its effective absorbance will be Ͼ0.6 [Wakakuwa et al (2004), their Fig. 4c].…”
Section: Mechanism Of Spectral Tuning By Fluorescing Pigmentmentioning
confidence: 99%
“…The R3 and R4 photoreceptors of both males and females are G photoreceptors, because of a visual pigment peaking at 563 nm, PrL. The proximal photoreceptors, R5-R8, of all ommatidia also express PrL, but depending on the pale-red or deep-red pigmentation around the rhabdom, the photoreceptors are red or deep-red photoreceptors, with very narrow sensitivity bands ϳ620 and ϳ640 nm (Wakakuwa et al, 2004). The latter spectral types presumably serve in the discrimination of subtle color changes of green leaves in the long-wavelength range.…”
Section: Molecular Design Of Butterfly Eyesmentioning
confidence: 99%
See 1 more Smart Citation
“…The eyes contain a few classes of randomly distributed ommatidia, with often a marked dorso-ventral regionalization (Arikawa and Stavenga 1997;Kitamoto et al 1998). A similar situation exists in the pierid butterfly Pieris rapae (Qiu et al 2002;Wakakuwa et al 2004) and the nymphalid Vanessa cardui (Briscoe et al 2003). Heterogeneity and regionalization seem to be general characteristics of butterfly eyes (Stavenga et al 2001;Warrant et al 2003).…”
Section: Introductionmentioning
confidence: 89%